On the Need of Improved Accelerated Degradation Protocols (ADPs): Examination of Platinum Dissolution and Carbon Corrosion in Half-Cell Tests. Issue 14 (5th November 2016) - Pizzutilo, E.; Geiger, S.; Grote, J.-P.; Mingers, A.; Mayrhofer, K. J. J.; Arenz, M.; Cherevko, S.
Abstract : In this work we employ the advanced scanning flow cell based analytical techniques, viz. inductively coupled plasma mass spectrometry (SFC-ICP-MS) and on-line electrochemical mass-spectrometry (SFC-OLEMS) to directly detect the amounts of dissolved platinum and evolved carbon dioxide in two protocols that are commonly used in the fuel cell community to simulate load cycle and start-stop conditions in proton exchange membrane fuel cells (PEMFCs). In contrast to previous assumptions, claiming a separation between carbon corrosion and platinum dissolution, in both standard protocols platinum dissolution and carbon corrosion are present at low rates, which is also reflected by a comparably low ECSA decrease. On the other hand, a huge increase in rate of both processes is observed during transitions from low to high potential regimes experienced by a PEMFC in operation, here studied in a third protocol covering the whole potential range from 0.6 to 1.5 VRHE . The latter is typically not addressed in literature. This finding is explained by taking into account platinum catalyzed carbon corrosion and transient platinum dissolution. Based on the obtained results, the question is raised on the practical adequacy of the standard protocols for differentiation of degradation processes and simulation of the degradation processes occurring in PEMFCs.